The South African national minimum wage conundrum : equality vs growth? - Schaling, Eric, 1962-; Mitchell, Clare (London : Wits Business School, 2017)
The case centres on the debate as to whether to implement a national minimum wage in South Africa. The increase of a national minimum wage in Brazil lead to a reduction in wealth inequality and higher living standards. However, there are fears that increasing the costs of employing and hiring workers for businesses may increase the unemployment rate already at 27% in 2016.
Originally Published InSchaling, E., & Mitchell, C. (2017). The South African national minimum wage conundrum: Equality vs growth? WBS-2017-10. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Minimum wage -- South Africa -- Case studies; Wages -- South Africa -- Case studies